Open-Source Software for Building-Integrated Photovoltaic Tiling for Novelty Architecture - Alexander W. H. Chin; Koami Soulemane Hayibo; Joshua M. Pearce (Designs)
Novelty architecture buildings can be tiled with conventional rectangular solar photovoltaic (PV) modules with both close-packed cells or partially transparent modules, vastly increasing renewable energy, reducing carbon emissions, and allowing for positive energy buildings. To enable this potential, in this study, for the first time, two open-source programs were developed and integrated to provide a foundation for designing and coating real-life novelty architecture buildings and objects with solar PV modules. First, a tiling algorithm was proposed and integrated into Blender that can generate solar PV modules on the face of any 3D model, and an augmented Python version of SAM was developed to simulate the performance of the resultant irregularly shaped PV systems. The integrated open-source software was used to analyze the energy performance of seven different novelty BIPVs located across the globe. The buildings’ energy performance was compared to conventional ground-based PV systems, and the results showed that the conventional arrays generate more energy per unit power than the BIPVs. The analysis reveals that the more complex the building model geometry, the less energy the building generates; however, the novelty BIPV power and energy densities far surpass conventional ground-based PV. The real estate savings observed were substantial, reaching 170% in one case where the BIPV reached 750 m in height. The BIPVs’ energy production is optimized by orienting the building via rotation and only needs to be carried out a single time for replication anywhere globally. The results show that the energy yield of the BIPV increases as the building becomes more detailed while the total power and energy decrease, indicating the need for the careful balancing of priorities in building design. Finally, the energy simulations demonstrate the potential for net-positive energy buildings and contribute to net-zero-emission cities. The findings indicate that BIPVs are not only appropriate for conventional residential houses and commercial buildings, but also for historical building replicas or monuments in the future. Further studies are needed to investigate the structural, electrical, and socio-economic aspects of novelty-architecture BIPVs.